Etnobotani Tumbuhan Liar Sebagai Alternatif Pangan oleh Masyarakat Dayak Pesaguan Desa Serengkah Kanan Kabupaten Ketapang - Anjeliana, Anjeliana; Syamswisna, Syamswisna; Yeni, Laili Fitri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Pesaguan Dayak people in Serengkah Kanan village, Ketapang Regency utilize wild plants as an alternative food.. The purpose of this study was to identify the types of wild plants used as food alternatives by the Dayak Pesaguan community in Serengkah Kanan Village, Ketapang Regency, West Kalimantan Province. Research using qualitative descriptive method. Data were collected by interviewing informants, making observations, and documentation. Plants used as food alternatives are identified to know their scientific names. Wild plants used as an alternative food by the Dayak Pesaguan community in Serengkah Kanan Village, Ketapang Regency are 37 species consisting of 23 families, namely Anacardiaceae, Arecaceae, Lamiaceae, Fabaceae, Malvaceae, Moraceae, Sapindaceae, Asteraceae, Achariaceae, Barseraceae, Phyllanthaceae, Apocynaceae, Euphorbiaceae, Olacaceae, Aracecae, Musaceae, Polypodiaceae, Talinaceae, Piperaceae, Araliaceae, Zingiberaceae, dilleniaceae, and menispermaceae. Leaves of the plant Pycnarrhena cauliflower D. and Premna corymbosa R. are used by the Dayak Pesaguan Tribe as an ingredient in food because they give a taste like micin and a distinctive aroma. The plant parts used are leaves, tubers, seeds, and fruits. The way of processing is sliced/cut into small pieces, inserted directly into food, mashed, boiled, sauteed, soaked in water before consumption, and some can be consumed directly.